Pengembangan Sistem Informasi Peminjaman, Pengembalian, dan Inventarisasi Alat Laboratorium Berbasis Web dengan Menggunakan Model Waterfall - Yunanda Rizki Sitompul; Triwanti Andini Hutasoit; Claudia Agatha Tarigan; Debi Yandra Niska (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Procedural inefficiency is a major challenge in administering laboratory equipment loans in academic environments, where paper-based processes are prone to recording errors and inventory data discrepancies. This condition directly impacts low asset accountability and the inability to monitor equipment availability status in real-time. This research focuses on the design and implementation of a website-based Laboratory Equipment Loan Information System (SIPINLAB) to provide an efficient, centralized, and accountable digital solution. The system development methodology uses the Waterfall Model approach, which is executed sequentially through the stages of requirements analysis, design, implementation, and testing. The technical implementation of SIPINLAB utilizes the PHP Native programming language and the MySQL database management system. The main findings of this study were confirmed through validation of the system's functionality using Black Box Testing in five main scenarios. The test results showed a 100% functional success rate, confirming that the system operates fully according to design specifications. This success validates the performance of SIPINLAB's crucial features, including the integration of automatic penalty calculations based on late returns and a real-time stock control mechanism that ensures data consistency. Overall, SIPINLAB successfully met its research objectives by transforming the manual loan process into a computerized one. This system's contribution minimizes the potential for human error and significantly improves laboratory asset management accountability through centralized, accurate, and valid transaction data.